Characterisation of recombinant Hevea brasiliensis allene oxide synthase: Effects of cycloxygenase inhibitors, lipoxygenase inhibitors and salicyclate on enzyme activity - Norton, Gareth; Pappusamy, Arokiaraj; Yusof, Faridah; Pujade-Renaud, Valerie; Perkins, Mark; Griffiths, David; Jones, Heddwyn (Elsevier, 2007)
Mechanical wounding and jasmonic acid (JA) treatment have been shown to be important factors in controlling laticifer differentiation in Hevea brasiliensis (rubber tree). With the long-term aim of potentially modifying the endogenous levels of JA in H. brasiliensis by gene transfer, we describe in this paper the molecular cloning of a H. brasiliensis allene oxide synthase (AOS) cDNA and biochemical characterisation of the recombinant AOS (His6-HbAOS) enzyme. The AOS cDNA encodes a protein with the expected motifs present in CYP74A sub-group of the cytochrome P450 super-family of enzymes that metabolise 13-hydroperoxylinolenic acid (13-HPOT), the intermediate involved in JA synthesis. The recombinant H. brasiliensis AOS enzyme was estimated to have a high binding affinity for 13-HPOT with a Km value of 4.02 ± 0.64 μM. Consistent with previous studies, mammalian cycloxygenase (COX) and lipoxygenase (LOX) inhibitors were shown to significantly reduce His6-HbAOS enzyme activity. Although JA had no effect on His6-HbAOS, salicylic acid (SA) was shown to significantly inhibit the recombinant AOS enzyme activity in a dose dependent manner. Moreover, it was demonstrated that SA, and various analogues of SA, acted as competitive inhibitors of His6-HbAOS when 13-HPOT was used as substrate. We speculate that this effect of salicylates on AOS activity may be important in cross-talking between the SA and JA signalling pathways in plants during biotic/abiotic stress.